2017
DOI: 10.1177/1010428317706479
|View full text |Cite
|
Sign up to set email alerts
|

Thymidine kinase 1 expression in ovarian serous adenocarcinoma is superior to Ki-67: A new prognostic biomarker

Abstract: Cancer is a disease with abnormally proliferating cells and therefore proliferation rate is an important index for assessing tumour growth. Ki-67 is a commonly used proliferation marker considered to be an unfavourable prognostic marker in some tumors, while Thymidine kinase 1 (TK1) is an interesting proliferation marker because its levels are highly dependent on the growth stage of cells. To define the immunohistochemistry (IHC) expression of the TK1 in patients with ovarian serous adenocarcinoma and establis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…Plasma or serum TKa has been shown to be a prognostic factor in other metastatic cancers [ 18 20 ]. Several studies have been conducted in various MBC settings using the same assay (DiviTum) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Plasma or serum TKa has been shown to be a prognostic factor in other metastatic cancers [ 18 20 ]. Several studies have been conducted in various MBC settings using the same assay (DiviTum) [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the latter may be inferred from the anti-VEGF action of ramucirumab to promote PG. We also analysed TK1, an alternative cell proliferation marker to Ki-67 9–11. We found many cells positive for TK1 by immunostaining, thus indicating the proliferation of vascular cells.…”
Section: Discussionmentioning
confidence: 92%
“…A clinical study conducted by Nisman et al in patient samples determined that increased levels of serum TK1 after first and second rounds of chemotherapy in nonsmall-cell lung cancer (NSCLC) and small-cell lung cancer (SCLC) was indicative of treatment failure and poor overall survival [96]. Huang et al and Wang et al also contributed to this theory when they showed that higher rates of occurrence and poorer overall survival of patients with locally advance breast cancer patients and ovarian serous adenocarcinoma patients who had abnormal levels of serum TK1 [98,99].…”
Section: Tk1 As a Tumor Biomarkermentioning
confidence: 99%